Effect of Intravenous Polyunsaturated Fatty Acids Administration on Gastric Mucosal Integrity in Pig-tailed Macaques with Obstructive Jaundice - Dadang Makmun; Dondin Sajuthi; Daldiyono Daldiyono; Adi Winarto; Erni Sulistiawati (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2011)
Background: Acute gastric mucosal injury commonly occurs in patients with obstructive jaundice. We studied the effect of intravenous polyunsaturated fatty acids (PUFA) administration on gastric mucosal integrity in pig-tailed macaques (Macaca nemestrina) with obstructive jaundice by ligating common bile duct (CBD). Method: The study was conducted between February 2009 and May 2010 at the Primate Research Center, Bogor Agricultural Institute. Eight selected male pig-tailed macaques with 6.625 ± 0.83 kg of body weight were used and divided into two groups. In both groups, laboratory examination, including liver function tests and upper gastrointestinal endoscopy were performed before CBD ligation and every two weeks after ligation. In the first group, intravenous PUFA with the dose of 2 g/day was administered every day since four weeks post-ligation up to four weeks later, and in the second group, intravenous PUFA was administered since before ligation up to eight weeks later. Results: In both groups, increased total bilirubin, direct bilirubin, indirect bilirubin, aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase and gamma glutamyl transpeptidase were obviously found, meanwhile decreased albumin level was detected and the cholinesterase level of both groups remained unchanged. Ulcer formation occurred among the first group during 4 weeks after CBD ligation, and these ulcers showed obvious healing within four weeks after intravenous PUFA administration. In the second group, there was no significant ulcer formation within eight weeks after CBD ligation. Conclusion: The potential appearance of acute gastric mucosal injury which reflected by ulcer formation in pig-tailed macaques with obstructive jaundice was significantly decreased by intravenous PUFA administration. We also have successfully developed animal model of obstructive jaundice by CBD ligation, based on the result of liver function tests. Keywords: acute gastric mucosal injury, intravenous PUFA administration, obstructive jaundice, pig- tailed macaques